An application of Six Sigma methodology for improving the first pass yield of a grinding process. Issue 1 (28th January 2014) - Gijo, E.V.; Antony, Jiju; Kumar, Maneesh; McAdam, Rodney; Hernandez, Jose
Abstract : Purpose: – The purpose of this paper is to illustrate the power of the Six Sigma methodology in improving the first pass yield of a high-precision grinding process in the manufacture of automotive products. Design/methodology/approach: – The paper follows a case study approach showing how theory has been put into practice. The case study was executed in a leading automotive company based in India. Findings: – The application of the Six Sigma methodology resulted in a reduction of tolerance-related problems and improved the first pass yield from 85 to over 99 per cent. A number of tools and techniques in the Six Sigma tool box have been utilised for data analysis and drawing valid and sound conclusions. The implementation of the Six Sigma methodology has demonstrated a saving of US$70, 000 in addition to the customer-facing benefits of improved quality on returns and sales. Practical implications: – The results of the case study have provided greater stimulus within the production facilities for wider application of the methodology as a powerful problem solving methodology. Moreover, this case study sets the foundation for many other projects within the business. Originality/value: – The paper is valuable to many Six Sigma black belts, practitioners of Six Sigma and researchers in terms of understanding the systematic application of the methodology in a real world situation.